The Effect of Badminton in Myopia Progression Among Children in Yogyakarta - Banu Aji Dibyasakti; Suhardjo Suhardjo; Tri Wahyu Widayanti; Zaenal Muttaqien (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2019)
Objectives : to observe the effect of badminton in myopia progression among children in Yogyakarta. Methods : This is a cohort study involving 139 eyes from 77 children. The subjects were divided into 2 groups: badminton (n=73) and control (n=66) group. The refractive error was measured by using auto- refractometer with additional cycloplegic agent (1% cyclopentolate). Myopia progression between baseline and 6 month follow up in each group were compared by using Paired T-Test Analysis. The difference of myopia progression in both group were compared by using Independent Sample T-Test Analysis. The relative risk of myopia progression by playing badminton was analysed by using 2x2 table analysis. Results : The mean refractive error in the badminton group was -1.03 ± 0.62 D (baseline) and -1.07 ± 0.64 D (6 months), while in the control group was -1.11 ± 0.66 D (baseline) and -1.24 ± 0.69 D (6 months). There was significant difference in the mean refractive error between baseline and 6 months in each group (p<0.05). Myopia progression in badminton group was 0.04 ± 0.10D, while in control group 0.12 ± 0.22. There was significant difference in myopia progression between two groups (p<0.05). Badminton is also significant protective factor against myopia progression in children (RR: 0.329 (0.157-0.687); p<0.05), even though another factor such as near-work, outdoors activities, and hereditary factor could confound the progression. Conclusion : Children who are routinely playing badminton show less myopia progression. There is statistically significance but not clinically significant difference in myopia progression between two groups. Playing badminton is a protective factor towards myopia progression